Reproductive performance and reconception of nellore cows according to their pure- or cross-bred calves - Rodrigues, W. B. [UNESP]; Wechsler, F. S. [UNESP]; Nogueira, E. (Wiley-Blackwell, 2015)
Contents The objective of the present research was to evaluate the effect of a calf's genetic group on the productive and reproductive efficiency of its Nellore dam. Fixed-time artificial insemination was applied to 800 cows using semen extracted from Nellore, Simmental and Angus Red bulls. Four hundred eleven cows calved, producing 119 Nellore, 103 1/2Simmental-1/2Nellore and 189 1/2Nellore-1/2Angus Red calves. The second mating period, which paired Nellore cows with Simmental bulls, was initiated 10days after parturitions began and lasted for 5months. Based on the two successive parturitions, the cumulative parturition rate for calving periods of 3, 4 and 5months was calculated. Although no significant difference was observed for birth weight among the genetic groups, cross-bred calves weighed, on average, 10% more than did pure-bred calves at the age of 205days. Nellore dams experienced a gestation period that was 7days longer than did the cross-bred dams, and the former showed a higher parturition rate at 90 and 120days of the calving season, but not at 150days (calving rates of 80.6, 76.4 and 76.2% for mothers of Nellore, 1/2Nellore-1/2Angus Red and 1/2Nellore-1/2Simmental, respectively, p>0.05). At 90 and 120days, Nellore dams produced more kg of calf per mated dam. In conclusion, in a short breeding season, Nellore dams nursing pure-bred Nellore calves were found to have a higher biological efficiency compared with Nellore dams nursing cross-bred calves.